The Effect of a Community Health Worker Utilized Mobile Health Application on Maternal Health Knowledge and Behavior: A Quasi-Experimental Study - Ilozumba, Onaedo; Van Belle, Sara; Dieleman, Marjolein; Liem, Loan; Choudhury, Murari; Broerse, Jacqueline E. W. (Frontiers in Public Health, 2018)
Background: Mobile technology (mHealth) is increasingly being used to achieve improved access and quality of maternal care, particularly in rural areas of low-and middle- income countries. In 2011, a mobile application-Mobile for Mothers (MfM), was implemented in Jharkhand, India to support home visits by Community health workers (CHW). The objective of this paper is to assess the impact of the mHealth intervention on maternal health. Methods: Households from 3 sub-districts in the Deoghar district of Jharkhand were selected using a multi-stage cluster sampling approach. Households from the Sarwan sub-district received the MfM intervention, those from Devipur sub-district received other interventions asides MfM from the implementing non-governmental organization (NGO), while households from Mohanpur sub-district received the current standard of care. Women (n=2200) between the ages of 18 and 45 who had delivered a baby in the past one year were enrolled into the study. The primary outcomes of interest were maternal health knowledge, antenatal care attendance, and delivery in a health facility. Results: Post-intervention, women in the MfM group had higher maternal health knowledge, were more likely to attend four or more ANC visits and deliver at the health facility when compared to the NGO and standard care group. After controlling for predictors, women in the intervention group significantly performed better than both the NGO and standard care groups on all three outcome variables (all p>0.05). Conclusion: The results indicate that although the MfM mHealth intervention could influence adherence and practice of recommended maternal health behaviours, it could not overcome key socio-cultural determinants of maternal health such as caste and educational status, which are specific to the Indian context. mHealth holds continued promise for maternal health but implementers and policy makers must additionally address health system and socio-cultural factors that play a significant role in the uptake of recommended maternal health practices.